Pengaruh Suhu Pengeringan Terhadap Mutu Teh Cascara dari Kulit Kopi Arabika (Coffea arabica) - Arinda Nur Ariva; Asri Widyasanti; Sarifah Nurjanah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2020)
One of the biggest plantation export commodities is coffee, with the number of products increasing every year. Arabica coffee (Coffea arabica) is the most widely produced in West Java with average production 9,736 tons from 2014 - 2018. The by-product of coffee production resulting in water and soil pollution due to high moisture content and polyphenol content which is toxic to soil. Reduction of coffee pulp waste could be done by making animal feed and cascara tea. The purpose of this study was to determine the effect of drying temperature using a convection oven on the characteristics of cascara tea quality. The drying temperatures used were 35 °C, 40 °C, 45 °C, 50 °C, and 55 °C. The research method used a laboratory experiment with descriptive analysis. The result showed that the difference in drying temperature could affect the characteristics of cascara tea quality. The best treatment was 45 °C of drying temperature with total yield was 6,61 ± 0,06 %, moisture content was 6,5705 ± 0,0272 % (w/w), ash content was 8,2107 ± 0,3195 % (w/w), polyphenol content was 14,2828 ± 0,2086 % (w/w). The organoleptic test result showed commercial cascara was ranked first with taste’s score was 3 (neutral), flavor’s score was 3 (neutral), and color’s score was 4 (like).